The Effect of Diet on Irritable Bowel Syndrome Symptoms and Its Role in the Treatment Plan (P12-001-19). (13th June 2019) - Adams, Rachel; Broughton, K Shane
Abstract: Objectives: Determine to what extent IBS patients relate their symptoms to diet and what role diet has in their treatment plan. Methods: Participants ages 18 to 65 with self-reported IBS were prospectively recruited to an online questionnaire study on IBS and diet administered through PsychData. Recruitment was through Texas Woman's University student, faculty, and staff and the researcher's social media accounts. Results: There were 148 completed surveys and 12 partial responses submitted. Around 57% ( n  = 85) of participants believe their IBS symptoms are related to what they eat with another 33% are unsure. Most participants (92%, n  = 133) attempted to manage their IBS with dietary changes with 81% ( n  = 122) currently avoiding foods due to sensitivities. Only 21 patients had attempted the Low FODMAP Diet, though many more avoid foods high in FODMAPs including wheat, dairy, soy, foods high in fructose, onions, garlic, and corn. Over half of participants (55%, n  = 62) reported that their doctor prescribed a specific diet or changes to their current diet to help manage their IBS. While 8 patients were referred to a RDN. only 6 actually consulted with one. Conclusions: Many physicians are not addressing diet in the context of IBS and few patients with IBS meet with RDNs. Thus, patients with IBS are largely self-managing their symptoms with diet and avoiding many foods due to perceived sensitivities. Funding Sources: Moore-Khourie Award from the Department of Nutrition, Texas Woman's University. Supporting Tables, Images and/or Graphs: